Koneksi Kekayaan-Perdamaian: HDI dan GPI di Negara-negara Timur Tengah - Djailani, Syahla Aurelya; Surwandono (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2023)
This study investigates the relationship between the Human Development Index (HDI) and the Global Peace Index (GPI) in the Middle East. This quantitative analysis employs the Pearson correlation coefficient formula, with HDI as the independent variable and GPI as the dependent variable. The literature review utilizes numerous sources, including journals, books, news media, and the internet. The research sample included Yemen, Afghanistan, Iraq, the United Arab Emirates (UAE), Palestine, Saudi Arabia, Syria, Qatar, and Israel. HDI and GPI are strongly negatively correlated (-0.854), indicating that an increase in one variable (HDI) diminishes the other variable (GPI). Consequently, countries in the Middle East with higher levels of human development tend to have lower GPI scores, indicating that higher levels of human development are associated with a greater likelihood of peace in this region.